2003
DOI: 10.1189/jlb.1003474
|View full text |Cite
|
Sign up to set email alerts
|

End-stage differentiation of neutrophil granulocytes in vivo is accompanied by up-regulation of p27kip1 and down-regulation of CDK2, CDK4, and CDK6

Abstract: The in vivo expression profiles of cell-cycle proteins regulating G1-to-S-phase transition were determined in three neutrophil precursor populations from human bone marrow: myeloblasts (MBs) and promyelocytes (PMs); myelocytes (MCs) and metamyelocytes (MMs); and band cells (BCs) and segmented neutrophil cells (SCs) and in mature polymorphonuclear neutrophils (PMNs) from peripheral blood. Complete cell-cycle arrest was observed in BCs/SCs and PMNs. Cyclins D1, D2, and D3 were found to be down-regulated during g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 64 publications
5
65
0
Order By: Relevance
“…The proliferation ceases as these cells mature into metamyelocytes, band cells, and segmented neutrophils. 21,22 The mitotic pool of immature neutrophil precursors in the bone marrow of Atg5 NΔ mice exhibited a significantly higher proliferation rate when compared with WT mice, whereas the proliferation rate of mature neutrophils was, as expected, comparably low in all genotypes (Figure 2b). Atg5 mRNA expression in these immature neutrophil populations was reduced by 75.3 ± 18.9% compared with WT mice (Figure 1a).…”
Section: Lyz2mentioning
confidence: 82%
“…The proliferation ceases as these cells mature into metamyelocytes, band cells, and segmented neutrophils. 21,22 The mitotic pool of immature neutrophil precursors in the bone marrow of Atg5 NΔ mice exhibited a significantly higher proliferation rate when compared with WT mice, whereas the proliferation rate of mature neutrophils was, as expected, comparably low in all genotypes (Figure 2b). Atg5 mRNA expression in these immature neutrophil populations was reduced by 75.3 ± 18.9% compared with WT mice (Figure 1a).…”
Section: Lyz2mentioning
confidence: 82%
“…19,30 Rapid down-regulation of p27 Kip1 is observed after stimulation with growth factors, when cells re-enter the cell cycle. 31 This suggests that IL-15MF and IL-15 tg MF are highly proliferating cells, which in addition are protected from apoptosis by IL-15.…”
Section: Il-15 Overexpression In Vivo Results In Highly Activated Mf mentioning
confidence: 99%
“…Reasoning that the enhanced MF activity leading to improved CD4 + T-cell stimulation could be the result of an altered expression of cell-cycle regulators, we next analysed the message expression (which correlates with the protein expression 19 ) of two critical cyclin-dependent kinase inhibitors. This revealed that p21 Waf1 , which protects MF from apop-tosis, 20 is expressed in MF and IL-15MF at comparable levels (Fig.…”
Section: Il-15 Regulates Expression Of the Cell-cycle Regulators P21 mentioning
confidence: 99%
“…44 Expression of these molecules in mature neutrophils is likely at a much lower level than in precursor cells, as CDK2, CDK4 and CDK6 protein expression is largely diminished in mature neutrophils as compared with promyelocytes. 47 Nevertheless, treatment of neutrophils with R-roscovitine, an inhibitor of CDK2, CDK7 and CDK9, results in neutrophil apoptosis ex vivo and in the resolution of inflammation in established animal models. 44 As R-roscovitine was subsequently shown to downregulate protein expression of Mcl-1, 45 this drug likely modulates neutrophil lifespan by controlling the expression of Bcl-2 family members.…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…44 This finding was surprising, as neutrophils were previously shown to downregulate Cdks during differentiation to mature cells. 47 A peptide of the Cdk inhibitor p21 was furthermore shown to interfere with binding of PCNA to pro-caspases and to induce neutrophil apoptosis in vitro. 46 Thus, this p21 peptide might be a potent inducer of neutrophil apoptosis through interaction with PCNA, but also Cdks.…”
Section: Bv6mentioning
confidence: 99%